2020
DOI: 10.1093/milmed/usz431
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Functional Outcome Predictors in Combat-Related Penetrating Brain Injury Treatment in a Specialty Civilian Medical Facility

Abstract: Introduction The combined use of new types of weapons and new types of personal protective equipment has led to changes in the occurrence, nature, and severity of penetrating brain wounds. The availability of modern equipment, methods of treatment, and trained medical personnel in a civilian hospital, as well as advanced specialty medical care, has improved treatment outcomes. There have been a limited number of publications regarding analysis and predictors of treatment outcomes in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
3
2
0
3
Order By: Relevance
“…In the current study, the GCS on admission was statistically significant lower in the non-survivor group as compared to the survivor group (p < 0.001). Our results come in agreement with Sirko et al (23) who showed that GCS score on admission is a predictor. Mortality was 44.7% in patients with GCS score of ≤ 8 on admission, whereas it was 5.4% in patients with GCS score of ≥ 9 on admission (P < 0.001).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, the GCS on admission was statistically significant lower in the non-survivor group as compared to the survivor group (p < 0.001). Our results come in agreement with Sirko et al (23) who showed that GCS score on admission is a predictor. Mortality was 44.7% in patients with GCS score of ≤ 8 on admission, whereas it was 5.4% in patients with GCS score of ≥ 9 on admission (P < 0.001).…”
Section: Resultssupporting
confidence: 94%
“…This agrees with El-Shanawany et al (12) who reported that missile injuries carry a worse prognosis than non-missile injuries as demonstrated by high mortality 45.8% to 16.6% respectively and that missile injuries carries a high incidence of morbidity to non-missile injuries. Sirko et al (23) also confirmed that patients with penetrating brain injury secondary to gunshot wound in our cohort had worse functional outcomes at all-time points than those who had blast penetrating brain injury.…”
Section: Resultssupporting
confidence: 82%
“…This case report is an example of the effective application of damage control surgery as well as transpapillary biliary decompression in the patient with multisystem causality in hybrid warfare. Furthermore, this case report provides new evidence of specific features of combat trauma and its management in the combat area of JFO in East Ukraine, which is consistent with previous publications [1,2,4,22]. In our opinion, this case report presents the evolution of the pathomorphosis of combat injury to the liver, which is associated with the improvement of high-energy weapons.…”
Section: Level IV -Highly-specialized Surgical Caresupporting
confidence: 89%
“…The military conflict in the East of Ukraine is characterized by the simultaneous use of modern personal protective equipment and new types of weapons, in particular rocket artillery, rocketpropelled grenades and landmines. This has led to an increase in the number of victims with blast injury and the need to provide them with effective assistance and rehabilitation [6].…”
Section: Introductionmentioning
confidence: 99%